Recovery of silica nanoparticles from waste PV modules. (2021) - Sapra, Gaurav; Chaudhary, Vikas; Kumar, Parveen; Sharma, Preetika; Saini, Anmol
Abstract: Recycling of PV modules to recover raw materials is much needed in current scenario. In this work, silica nanoparticles are recovered from discarded PV modules using chemical and thermal treatment. I-V characteristics are performed to determine the type of doping on the front and back surface of silicon wafer. XRD characterisation is performed to find the orientation of recovered silicon. Further silica nanoparticles is synthesised from silicon wafer and result obtained is in agreement with UV–vis spectrophotometry. The use of waste PV modules as mobile charger is also discussed. This work will set new pathways for developing a PV module waste management industry which enhances the supply of future raw material requirement.